2016
DOI: 10.1111/evo.13074
|View full text |Cite
|
Sign up to set email alerts
|

Sexual selection expedites the evolution of pesticide resistance

Abstract: The evolution of insecticide resistance by crop pests and disease vectors causes serious problems for agriculture and health. Sexual selection can accelerate or hinder adaptation to abiotic challenges in a variety of ways, but the effect of sexual selection on resistance evolution is little studied. Here, we examine this question using experimental evolution in the pest insect Tribolium castaneum. The experimental removal of sexual selection slowed the evolution of resistance in populations treated with pyreth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 44 publications
4
25
0
Order By: Relevance
“…The results from females assayed with enforced monogamy suggest that sexual selection is acting to enhance the promotion of beneficial alleles within a population and facilitate adaptation to increasing temperatures through 'good genes' mechanisms of sexual selection. This indicates that when the environment changes continuously, sexual selection can provide similar benefits to those found by previous empirical studies which examined the effect of sexual selection on adaptation when the environment undergoes a step change [25][26][27]. In this case, however, the improved fitness associated with strong sexual selection was not sufficient to delay extinction as temperatures continuously increased.…”
Section: Discussionsupporting
confidence: 64%
“…The results from females assayed with enforced monogamy suggest that sexual selection is acting to enhance the promotion of beneficial alleles within a population and facilitate adaptation to increasing temperatures through 'good genes' mechanisms of sexual selection. This indicates that when the environment changes continuously, sexual selection can provide similar benefits to those found by previous empirical studies which examined the effect of sexual selection on adaptation when the environment undergoes a step change [25][26][27]. In this case, however, the improved fitness associated with strong sexual selection was not sufficient to delay extinction as temperatures continuously increased.…”
Section: Discussionsupporting
confidence: 64%
“…Evidence that sexual selection helps to fix beneficial alleles more effectively when environments change also varies, with some studies reporting that sexual selection improves adaptation to a novel environment (Fricke and Arnqvist ), aids the evolution of pesticide resistance (Jacomb et al. ), or prevents extinction (Plesnar‐Bielak et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In a mutation accumulation study with D. serrata, sexual selection did not prevent fitness reductions associated with the buildup of load, but did strengthen the fitness correlation between males and females, indicating an importance for sex-limited genetic load for population fitness (Allen et al 2017). Evidence that sexual selection helps to fix beneficial alleles more effectively when environments change also varies, with some studies reporting that sexual selection improves adaptation to a novel environment (Fricke and Arnqvist 2007), aids the evolution of pesticide resistance (Jacomb et al 2016), or prevents extinction (Plesnar-Bielak et al 2012). However, others have found no equivalent benefit (Holland 2002;Rundle et al 2006) or even antagonism against adaptation (Chenoweth et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Theory indicates that when there is strong reproductive skew sexual selection can increase adaptation rates to novel environments: if the skew is in favour of 'high quality' individuals this enhances the spread of adaptive alleles throughout a population (Lorch et al 2003;Mart ınez-Ruiz & Knell 2017). Consistent with this theory, laboratory studies using invertebrate model organisms in experimental evolution designs have found that sexual selection enhances adaptation and protects against extinction (Fricke & Arnqvist 2007;Long et al 2012;Plesnar-Bielak et al 2012;Jacomb et al 2016;Parrett & Knell 2018;Yun et al 2018). Similarly, sexual selection has also been found to enhance the removal of deleterious alleles and to reduce the probability of extinction from inbreeding depression (Jarzebowska & Radwan 2010;Lumley et al 2015).…”
Section: Introductionmentioning
confidence: 98%